2007
DOI: 10.1097/gme.0b013e318057786b
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone correlated to symptoms of partial androgen deficiency in aging men (PADAM) in an elderly Swedish population

Abstract: Symptoms associated with PADAM often occur in an elderly population, but we could only find an association between three symptoms and blood testosterone concentrations, one being bothersome hot flushes. It is likely that these symptoms have a more complex background than only PADAM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 23 publications
8
30
3
Order By: Relevance
“…The questionnaire was modified from previously used and validated questionnaires developed by us (29)(30)(31). To test comprehension, six women, 47-56 years old, were asked to answer the questionnaire in writing.…”
Section: Cross-sectional Study Performed In 2010mentioning
confidence: 99%
“…The questionnaire was modified from previously used and validated questionnaires developed by us (29)(30)(31). To test comprehension, six women, 47-56 years old, were asked to answer the questionnaire in writing.…”
Section: Cross-sectional Study Performed In 2010mentioning
confidence: 99%
“…In a cross-sectional study of men in Sweden, performed in 2003, we investigated the prevalence of probable symptoms of LOH and associated them with testosterone concentrations [12]. We found that symptoms associated with LOH often occur in an elderly population, but we could only find an association between three symptoms and blood testosterone concentrations, one being bothersome hot flushes why we suggest that hot flushes should be addressed as a possible LOH-symptom.…”
Section: Partial Androgen Deficiency In Aging Males (Padam) or Androgmentioning
confidence: 82%
“…Since we have previously investigated possible symptoms of LOH and measured T and BT in men 55 to 75 years old [12,13], and since the decline in androgens seems to begin earlier than previously believed, i.e. at approximately age 30 [3], we wanted to investigate symptoms of testosterone deficiency and androgen concentrations in a an even younger group of men.…”
Section: Partial Androgen Deficiency In Aging Males (Padam) or Androgmentioning
confidence: 99%
See 1 more Smart Citation
“…56 In comparison with clinically well-defined menopause, andropause symptoms would be rather subtle and seem to affect sexual functions, bone and muscle mass, body composition, and cardiovascular health and results in mood and cognitive disorders. 55 However, it is important to state that some men have a lower than normal T level without signs or symptoms.…”
Section: Lang Et Al Clinical Meaningfulness Of T Decline In Older Menmentioning
confidence: 99%